Muslims in Pioneering Modern Knowledge: Chronicles of The Freely or Unconsciously Surrendered Legacies To The West - Abdulrahman Yusuf Maigida (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The paper dwelt on exemplification of the role of early Muslim world in pioneering modern knowledge with a magnification of the legacies that these torchbearers in Islam bequeathed to the world. The peculiarity of Nigeria as a nation with more than half of its entire population as Muslims was retrospectively reviewed from the pre-colonial to colonial-era; focusing on scholasticism. The study was examined purely from the historical perspective, to appraise how the impressive efforts of the early Muslim pioneers of modern knowledge in Medicine, Chemistry, Physics, Astronomy, Geometry, Mathematics, History, Geography and Biological Sciences were undertaken. The study did not finish without the expression of concern on how the golden legacies of the early Muslim pioneers have been played down by the Muslims of today, where knowledge or groundbreaking discoveries are now credited to the West, making it look like stolen legacies or freely surrendered legacies to those who are currently worried about the development. Based on these genuine concerns, several wells thought out recommendations were penned down, not limited to a suggestion on growing above externally triggered wars and hostilities among Muslim nations, and giving peace and unity chance, to settle down to reflect on how sustainable progress can be achieved in the world of knowledge economy.